A look into the disclosure improvements of CSR reporting in Bangladesh / Nikhil Chandra Shil and Alok Kumar Pramanik - Shil, Nikhil Chandra (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
Corporate social responsibility (CSR) reporting is an embracing issue today that becomes the social perspective of accounting and reporting. Still, the international standard setters are lagging behind to bring this issue within the legal framework of accounting and reporting. As there is a huge demand from the stakeholders for such information, it becomes a common area of voluntary disclosure at the time of reporting. The paper targets to highlight the improvement of CSR reporting in Bangladesh over a period of six (6) years through the content analysis of financial statements of DSE 20 companies. Content analysis has helped us to identify a couple of common categories where most of the firms do social reporting. The analysis was based on secondary sources of information; i.e., published financial statements of DSE 20 companies for the year 2000 and 2006. Different descriptive statistics were used to organize and analyze the findings of the study. It concluded that the pattern of such reporting was far away from expectation; still, there was a positive indication that the volume and quality of reporting was increasing.